2016
DOI: 10.56454/hxyt5212
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Pubescence and Defoliation Strategy Influence on Cotton Defoliation and Fiber Quality

Abstract: Proper defoliation of cotton is critical to maximize both harvest efficiency and fiber quality. Increased levels of leaf grade or trash resulting from inadequate defoliation can lead to decreases in fiber quality and value. Inherent characteristics of cultivars, such as leaf pubescence levels and defoliation practices influence the efficacy of cotton defoliation. This study aimed to determine the impact of leaf pubescence and defoliation strategies on defoliation success and fiber quality in cotton. Treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The defoliation timing, strategy, and leaf pubescence characteristics can impact the efficacy of defoliation and the fiber quality parameters [37,38]. There were several studies on cotton fiber quality assessment [39][40][41][42]; however, no information is available on the effects of defoliant dosage with the application of cotton defoliation with side spraying covering the whole canopy of the plant (i.e., bottom, middle, and upper).…”
Section: Fiber Quality Analysis By Hvimentioning
confidence: 99%
“…The defoliation timing, strategy, and leaf pubescence characteristics can impact the efficacy of defoliation and the fiber quality parameters [37,38]. There were several studies on cotton fiber quality assessment [39][40][41][42]; however, no information is available on the effects of defoliant dosage with the application of cotton defoliation with side spraying covering the whole canopy of the plant (i.e., bottom, middle, and upper).…”
Section: Fiber Quality Analysis By Hvimentioning
confidence: 99%
“…The translocation of systemic herbicides may be the main mechanism that nullifies the effect of the droplet size and lower leaf coverage . The above studies on insecticides, fungicides, and herbicides have shown that the deposition effect and behavior of pesticide droplets have a significant impact on drug efficacy. …”
Section: Introductionmentioning
confidence: 99%